OPTIMALISASI KOMPOSISI RANSUM UNGGAS BERBASIS LIMBAH SAWIT - Husein, Firdaus; Dilfa, Muhammad; Nisfimawardah, Lailatun; Riskayanti, Riskayanti; Monasdir, Monasdir; Astuti, Erlina (AGRIBIOS, 2024)
Polutry farming in Central Kalimantan has shown a positive trend in the last 3 years. The increase in chicken farming causes the use of livestock rations to increase. Feeding is the largest contributor to production costs in the chicken farming industry, contributing 70-80% of production costs. The current increase in feed prices means that farmers have to look for new innovations to overcome this problem, where the price of animal feed rations is relatively cheaper and the nutrition obtained by livestock is still achieved. The innovation that can be used is using palm oil waste as a substitute for corn and rice bran. Palm kernel meal (BIS) is a by-product of the palm oil industry where the nutritional content obtained by BIS is very suitable as an alternative animal feed in terms of nutritional content and is easy to obtain at a relatively cheaper price. However, there is no model for formulating animal feed rations. So in this research, a model of animal feed ration formulation was created using the linear programming method to determine the optimal composition for preparing this animal feed ration. The objective function of this model is to minimize the price of animal feed rations. Before the model is used, model verification and validation is carried out which is useful for testing logical suitability and compatibility with the real system. The results of the model that has been created can reduce the cost of producing animal feed rations is 11%, which is the actual condition Rp. 6,800 and the model obtained is Rp. 6,114 where the nutrition obtained is relatively the same as actual conditions. Keywords: Palm Kernel Meal, Production Costs, Nutritional Requirements, Minimization.